Ultrasound‐guided fine needle aspiration cytology in the diagnosis of hepatic and pancreatic perivascular epithelioid cell tumors: A case series. Issue 4 (12th November 2018) - Sangiorgio, Valentina; Daniele, Lorenzo; Gallo, Teresa; Rocca, Rodolfo; Fava, Cristina; Campisi, Paola; De Rosa, Giovanni
Abstract : Perivascular epithelioid cell tumors (PEComas) are rare mesenchymal tumors that can affect any part of the body. They can be sporadic or arise in the setting of tuberous sclerosis (TSC). In this article, we report a series of three hepatic and two pancreatic PEComas diagnosed preoperatively with ultrasound‐guided fine needle aspiration (FNA). All patients were female (age range 28‐70), had no personal history of TSC and presented with a single, localized painless mass. Rapid on‐site evaluation (ROSE) of cytologic samples was performed for all cases to evaluate for cellular content and adequacy of specimens. Direct smears and cell block preparations revealed a proliferation of medium to large polygonal epithelioid cells, with abundant eosinophilic and vacuolated cytoplasm, arranged in sheets and nests. On immunohistochemistry (IHC), neoplastic cells showed co‐expression of melanocytic and smooth muscle markers and a diagnosis of PEComa was rendered. PEComas of the pancreas and liver are rare neoplasms, but should always be considered when examining "clear cell" neoplasms, especially in young female patients. If good quality cytologic samples are obtained by FNA, a correct diagnosis can be achieved with the help of IHC. This is of particular importance in order to plan adequate surgical strategy and to avoid overtreatment.